Family Experience in Caring for Patients with Chronic Renal Failure: Literature Review - Indra Prasetyantoro; Nur Chayati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background:Chronic kidney failure is a chronic disease that requires special attention and is one of the highest causes of death in the world. Patients with chronic renal failure are unable to cope with and meet their own physical, psychological and financial needs, thus becoming a burden on the family/caregiver. Objective: The study examines through a literature review of family experiences in caring for family members suffering from chronic renal failure. Method: Literature Search using PubMed, EBSCO, Scopus, and ProQuest search engine databases in November 2022 using the keywords experience, family caregiver, and chronic renal failure. Researchers took 2012-2022 articles by looking at titles, abstracts, and full text to assess the journal's feasibility. Result:A total of 5 articles and 249 respondents out of 2289 articles were found and used. Researchers discover and conclude the importance of the role of the family in helping physical needs, providing emotional and psychological support, supporting economic needs, advocacy and navigation. Conclusion:Family stress/burdens include physical exhaustion, fatigue and emotional baggage, tension and anxiety. Families also experience impaired roles of taking responsibility as well as roles of care in children and family members.Abstrak: Latar Belakang: Penyakit gagal ginjal kronis merupakan penyakit kronis yang membutuhkan perhatian khusus dan menjadi salah satu penyebab kematian tertinggi di dunia. Pasien dengan gagal ginjal kronis tidak dapat mengatasi dan memenuhi kebutuhan fisik, psikologis dan finansialnya sendiri, sehingga menjadi beban keluarga/caregiver. Tujuan: Penelitian mengkaji melalui telaah literatur tentang pengalaman keluarga dalam merawat anggota keluarga yang menderita gagal ginjal kronis. Metode: Penelusuran Literatur menggunakan database search enginer PubMed, EBSCO, Scopus, dan ProQuest pada November 2022 menggunakan kata kunci experience, family caregiver, dan chronic renal failure. Peneliti mengambil artikel tahun 2012-2022 dengan melihat judul, abstraks, dan teks lengkap untuk menilai kelayakan jurnal. Sebanyak 5 artikel dan 249 responden dari 2289 artikel ditemukan dan digunakan. Hasil: Peneliti menemukan dan menyimpulkan pentingnya peran keluarga dalam membantu kebutuhan fisik, pemberi dukungan emosional dan psikologi, pendukung kebutuhan ekonomi, advokasi dan navigasi. Kesimpulan:Tekanan/beban keluarga meliputi kelelahan fisik, kelelahan dan beban emosional, ketegangan dan kecemasan. Keluarga juga mengalami gangguan peran pengambilan tanggung jawab serta peran perawatan pada anak dan anggota keluarga.